Three-Dimensional Patient-Derived In Vitro Sarcoma Models: Promising Tools for Improving Clinical Tumor Management - Gaebler, Manuela; Silvestri, Alessandra; Haybaeck, Johannes; Reichardt, Peter; Lowery, Caitlin D.; Stancato, Louis F.; Zybarth, Gabriele; Regenbrecht, Christian R. A. (Frontiers in Oncology, 2017)
Over the past decade, the development of new targeted therapeutics directed against specific molecular pathways involved in tumor cell proliferation and survival has allowed an essential improvement in carcinoma treatment. Unfortunately, the scenario is different for sarcomas, a group of malignant neoplasms originating from mesenchymal cells, for which the main therapeutic approach still consists in the combination of surgery, chemotherapy and radiation therapy. The lack of innovative approaches in sarcoma treatment stems from the high degree of heterogeneity of this tumor type, with more that 70 different histopathological subtypes, and the limited knowledge of the molecular drivers of tumor development and progression. Currently, molecular therapies are available mainly for the treatment of gastrointestinal stromal tumor, a soft tissue malignancy characterized by an activating mutation of the tyrosine kinase KIT. Since the first application of this approach, a strong effort has been made to understand sarcoma molecular alterations that can be potential targets for therapy. The low incidence combined with the high level of histopathological heterogeneity make the development of clinical trials for sarcomas very challenging. For this reason, pre-clinical studies are needed to better understand tumor biology with the aim to develop new targeted therapeutics. Currently these studies are mainly based on in vitro testing, since cell lines, and in particular patient-derived models, represent a reliable and easy to handle tool for investigation. In the present review we summarize the most important models currently available in the field, focusing in particular on the three-dimensional spheroid/organoid model. This innovative approach for studying tumor biology better represents tissue architecture and cell-cell as well as cell-microenvironment crosstalk which are fundamental steps for tumor cell proliferation and survival.